MEANS FOR INHIBITION OF PRODUCTION OF STAPHYLOCOCCUS ENTEROTOXINS AND THEIR ELIMINATION FROM BIOLOGICAL SUBSTRATES - F. S. Fluer; A. V. Kudryavtseva; S. I. Titarev; I. B. Bykova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Expansion of arsenal of means capable of inhibiting production of staphylococci entero-toxins (SE) and having an ability to eliminate them from biological substrates, as well as reducing the growth of staphylococci. Materials and methods. Reference strain of Staphylococcus aureus FRI 722 was used as SE producer type A (SEA), S. aureus S6 715H - as SE type В producer (SEB). Polymethylsiloxane polyhydrate (PMSPH) was used at concentrations of 1.82, 9.09 and 18.2%. Results. By using gel double diffusion method and ELISA we have established that a 18.2% solution of PMSPH (enterosgel; PMSPH - 70 g, purified water - 30 g per 100 g of the product) is an optimal concentration for inhibition of production of staphylococcus enterotoxin type A by 100 and more times, and production of staphylococci enterotoxin type В - by more than 300 times. Conclusion. PMSPH is able to eliminate staphylococci enterotoxins type A and В from biological substrates for more than 50% and significantly reduce growth of staphylococci.